A maximum principle for constrained infinite horizon dynamic control systems - Pereira, Fernando Lobo; Silva, Geraldo Nunes [UNESP] (Elsevier, 2011)
This article presents and discusses a maximum principle for infinite horizon constrained optimal control problems with a cost functional depending on the state at the final time. The main feature of these optimality conditions is that, under reasonably weak assumptions, the multiplier is shown to satisfy a novel transversality condition at infinite time. It is also shown that these conditions can also be obtained for impulsive control problems whose dynamics are given by measure driven differential equations. © 2011 IFAC.
Keywords: Impulse control; Maximum principle; Optimal control; Constrained optimal control problems; Cost functionals; Dynamic control systems; Impulsive controls; Infinite horizons; Infinite time; Optimal controls; Optimality conditions; Transversality conditions; Differential equations; Optimal control systems